Study on Skin Factor and Productivity of Horizontal Well after Acidizing with Nonuniform Damage - Lin Yuan; Xiao-Ping Li; Xiao-Hua Tan; Lie-Hui Zhang (Journal of Chemistry)
Horizontal well (HW) was divided into several elements after acidizing. In each element, there would exist a composite zone that was made up of damage zone (DZ) and acidizing zone (AZ). Local skin factor after acidizing was used to describe the resistance in each composite zone. The models for local skin factor and productivity of HW were created using the method of equivalent filtration resistance and displacement between two similar flow modes. According to the solution of the models, type curves of skin factor and production-increasing ratio after acidizing were illustrated, and the effect of different parameters in DZ and AZ on distribution of skin factor and production-increasing ratio after acidizing were discussed. The present model has a significant guide on the practice of acidizing technology.